The effect of Melatonin on Improving the benign Prostatic Hyperplasia Urinary Symptoms, a Randomized Clinical Trial - Fotovat, Amirreza; Samadzadeh, Bahram; Ayati, Mohsen; Nowroozi, Mohammad Reza; Momeni, Seyed Ali; Yavari, Samira; Nasseri, Ali; Sharifi, Laleh (Urology Journal, 2022)
Purpose: to investigate the effect of melatonin along with tamsulosin in improving BPH urinary symptoms. Materials and Methods: A total of 108 men with BPH symptoms, age of ≥ 50 years, and International Prostate Symptom Score (IPSS) ≥ 8 entered into the parallel group randomized, double-blind clinical trial with balanced randomization. The treatment group received of 3mg melatonin plus 0.4mg tamsulosin and the control group received placebo plus 0.4mg tamsulosin. Patients and physicians were concealed by sealed and opaque envelopes. Symptoms were assessed at baseline and 1 month after treatment. Finally all scores at the initial and end of the study were compared and analyzed using SPSS software. Results: This study showed that adding melatonin to the classic treatment of BPH patients with tamsulosin could significantly reduce the likelihood of nocturia by 2.39 times (95% CI: 1.07-5.32, OR = 2.39, p = 0.033) and could also reduce the frequency of urination by 2.59 times (95% CI: 1.15-5.84, OR = 2.59, p = 0.021). There was no statistically significant difference between the two groups in IPSS, intermittency, incomplete emptying, straining, urgency, and weak stream. Conclusion: Melatonin plus tamsulosin treatment is associated with a significant improvement of nocturia and frequency in patients with benign proststic hyperplasia. However, it is necessary to do more studies.